2018
DOI: 10.1159/000487796
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Small Bowel Lesions Using Capsule Endoscopy in Ulcerative Colitis and Crohn’s Disease: A Single-Center Retrospective Analysis

Abstract: Background: Capsule endoscopy (CE) has allowed the characterization of small bowel lesions. However, small bowel lesions in ulcerative colitis (UC) have not been elucidated and no studies have compared between UC and Crohn’s disease (CD). Aim: The objective of this study was to investigate the small bowel lesions in UC, and to characterize UC lesions by comparison with CD. Methods: Subjects comprised 54 UC patients and 39 CD patients who underwent CE. We retrospectively investigated characteristics of small bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“… 72 reported that 36% of lesions of a patient with UC were detected in the SB, as well as 27.8% of patients also reported by Ninomiya et al. 73 We believe that the CE is also a useful device to identify injuries that could occur in the SB in patients with UC.…”
Section: Ce In CDsupporting
confidence: 55%
See 1 more Smart Citation
“… 72 reported that 36% of lesions of a patient with UC were detected in the SB, as well as 27.8% of patients also reported by Ninomiya et al. 73 We believe that the CE is also a useful device to identify injuries that could occur in the SB in patients with UC.…”
Section: Ce In CDsupporting
confidence: 55%
“…69 Oliva et al 70 reported a higher diagnostic accuracy of the CCE-2 during the evaluation of disease activity compared with CS in pediatric patients, also confirmed by Shi et al in a large-scale prospective study. 71 Interestingly, Hisabe et al 72 reported that 36% of lesions of a patient with UC were detected in the SB, as well as 27.8% of patients also reported by Ninomiya et al 73 We believe that the CE is also a useful device to identify injuries that could occur in the SB in patients with UC.…”
Section: Ce In Ucmentioning
confidence: 72%
“…[ 22 ] UC is restricted to the colon; however, a few cases of UC with gastroduodenal lesions and small bowel lesions have also recently been reported. [ 23 25 ] In our study, 180 patients were diagnosed with IBD (160 CD, 20 UC). In children with IBD, VCE can be used to investigate the parts of the small bowel that cannot be observed by gastroscopy and colonoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…We searched the PubMed and Embase databases using the terms "ulcerative colitis" and "post-colectomy enteritis" or "pan-enteritis" or "diffuse enteritis" or "pre-stomal enteritis" or "small bowel lesion" in English before June 1, 2020. Thirty-seven cases were previously reported [10][11][12][13][14][26][27][28][29][30][31][32]. This rare disease with distinct endoscopic inflammation of the stomach and small bowel resembles inflammation in the colon with UC.…”
Section: Discussionmentioning
confidence: 99%